Applicability of Workplace-Based Assessment tools (Mini-CEX) for the trainee doctors of Obstetrics and Gynecology in Bangladesh - Akhee, Hasna Hossain; Sultana, Nazma (Bangladesh Journal of Medical Education, 2023)
This cross-sectional study was conducted to assess the applicability of workplace-based assessment tools (Mini-CEX) for the trainee doctors of Obstetrics and Gynecology in Bangladesh. The study was conducted from January 2022 to December 2022. The Study population were trainee of selected medical college hospital and Supervisors/Teachers of selected medical college hospital. Medical colleges were selected conveniently. Respondents were selected purposively. Research instruments were Mini-CEX, questionnaire of American Board of Internal Medicine. Scores were given to each scale as: unsatisfactory=1 2 3, satisfactory =4 5 6, superior=7 8 9. Bangladesh Journal of Medical Education Vol.14(2) July 2023: 56-59